Neutrophil-like cell membrane-coated siRNA of lncRNA AABR07017145.1 therapy for cardiac hypertrophy via inhibiting ferroptosis of CMECs - Pilong Shi (Elsevier, 2022)
Cardiac microvascular dysfunction is associated with cardiac hypertrophy and can eventually lead to heart failure. Dysregulation of long non-coding RNAs (lncRNAs) has recently been recognized as one of the key mechanisms involved in cardiac hypertrophy. However, the potential roles and underlying mechanisms of lncRNAs in cardiac microvascular dysfunction have not been explicitly delineated. Our results confirmed that cardiac microvascular dysfunction was related to cardiac hypertrophy and ferroptosis of cardiac microvascular endothelial cells (CMECs) occurred during cardiac hypertrophy. Using a combination of in vivo and in vitro studies, we identified a lncRNA AABR07017145.1, named as lncRNA AAB for short, and revealed that lncRNA AAB was upregulated in the hearts of cardiac hypertrophy rats as well as in the Ang II-induced CMECs. Importantly, we found that lncRNA AAB sponged and sequestered miR-30b-5p to induce the imbalance of MMP9/TIMP1, which enhanced the activation of transferrin receptor 1 (TFR-1) and then eventually led to the ferroptosis of CMECs. Moreover, we have developed a delivery system based on neutrophil membrane (NM)-camouflaged mesoporous silica nanocomplex (MSN) for inhibition of cardiac hypertrophy, indicating the potential role of silenced lncRNA AAB (si-AAB) and overexpressed miR-30b-5p as the novel therapy for cardiac hypertrophy.